The oculoauriculofrontonasal syndrome: Further clinical characterization and additional evidence suggesting a nontraditional mode of inheritance. Issue 12 (10th December 2018) - Lehalle, Daphné; Altunoglu, Umut; Bruel, Ange‐Line; Assoum, Mirna; Duffourd, Yannis; Masurel, Alice; Baujat, Geneviève; Bessieres, Bettina; Captier, Guillaume; Edery, Patrick; Elçioğlu, Nursel H.; Geneviève, David; et al.
Abstract: The oculoauriculofrontonasal syndrome (OAFNS) is a rare disorder characterized by the association of frontonasal dysplasia (widely spaced eyes, facial cleft, and nose abnormalities) and oculo‐auriculo‐vertebral spectrum (OAVS)‐associated features, such as preauricular ear tags, ear dysplasia, mandibular asymmetry, epibulbar dermoids, eyelid coloboma, and costovertebral anomalies. The etiology is unknown so far. This work aimed to identify molecular bases for the OAFNS. Among a cohort of 130 patients with frontonasal dysplasia, accurate phenotyping identified 18 individuals with OAFNS. We describe their clinical spectrum, including the report of new features (micro/anophtalmia, cataract, thyroid agenesis, polymicrogyria, olfactory bulb hypoplasia, and mandibular cleft), and emphasize the high frequency of nasal polyps in OAFNS (56%). We report the negative results of ALX1, ALX3, and ALX4 genes sequencing and next‐generation sequencing strategy performed on blood‐derived DNA from respectively, four and four individuals. Exome sequencing was performed in four individuals, genome sequencing in one patient with negative exome sequencing result. Based on the data from this series and the literature, diverse hypotheses can be raised regarding the etiology of OAFNS: mosaic mutation, epigenetic anomaly, oligogenism, or nongenetic cause. In conclusion, this series represents further clinical delineation work of the rare OAFNS, and paves the way toward the identification of the causing mechanism.